Cariprazine as a Treatment Option for Depressive Episodes Associated with Bipolar 1 Disorder in Adults: An Evidence-Based Review of Recent Data - Tohen M (Dove Medical Press, 2021)
Mauricio Tohen Department of Psychiatry and Behavioral Sciences, University of New Mexico, Albuquerque, NM, USACorrespondence: Mauricio TohenDepartment of Psychiatry and Behavioral Sciences, University of New Mexico, 2400 Tucker Ave NE, MSC09 5030, Albuquerque, NM, 87131, USAEmail mtohen@salud.unm.eduAbstract: Depressive episodes, the most frequent episodes in bipolar disorder, contribute in large part to poor functional outcomes. Very few treatments, however, have been approved by the Food and Drug Administration for the treatment of bipolar depression. Cariprazine, a broad-spectrum dopamine antagonist/partial agonist with dopamine D3/D2 (preferring D3) and serotonin 5-HT1A receptor partial agonist properties, was recently approved. A review of the literature suggests that it is an effective and well-tolerated treatment for bipolar depression.Keywords: Cariprazine, bipolar depression, antipsychotics, psychopharmacology